Probiotic innovations: bacillus species in dermatology and cosmetology - Yana Yemchenko; Kateryna Bardova; Oleh Akimov; Anatolii Levkov; Heorhii Kostenko; Viktoriia Kostenko; Artur Mishchenko; Natalia Solovyova; Vitalii Kostenko (Sociedade Brasileira de Dermatologia (SBD), 2024)
In recent years, the use of probiotics in dermatology and cosmetology has been demonstrating a notable rise, offering both preventive and therapeutic benefits for the skin. The intestinal microbiota plays crucial roles, including enzymatic degradation of dietary fiber, starch, proteins, and fats, as well as the synthesis of vitamins B, K, nicotinic acid, amino acids, and various metabolites. The use of multicomponent probiotics composed of strains of the genus Bacillus is a promising way to optimize the positive effects of these microorganisms in dermatological and cosmetic practice and avoid their undesirable effects.